Hybrid numerical modeling of reverberation chambers - Zhao, Huapeng (2012)
This thesis deals with the efficient modeling of a full-scale reverberation chamber (RC), and a hybrid technique combining the discrete singular convolution (DSC) method and method of moments (MoM) is proposed to overcome difficulties in RC modeling. An RC is constituted by a large rectangular cavity, in which stirrers and antennas are mounted/stationed. The large cavity is usually of rectangular shape, while stirrers and antennas are arbitrarily shaped and oriented. In this thesis, the hybrid method utilizes the DSC method for the efficient modeling of the large cavity, and applies the MoM to simulate stirrers and antennas. Using higher-order basis, the DSC method can obtain better accuracy using coarser grids compared to the conventional finite difference method. In this way, the number of unknowns is greatly reduced. However, the DSC method is not flexible in modeling structures of arbitrary shape. This is because structured grids are usually used to discretize the computational domain. Meanwhile, using coarse grids further reduces the flexibility of the DSC method. The inflexibility of the DSC method is complemented by MoM in the proposed hybrid method. A Huygens' box is used to enclose a stirrer, and Huygens' principle is applied to obtain fields illuminating the stirrer. The induced current on the stirrer can be solved using MoM, and it is considered as a secondary source for the large cavity. The antenna is treated in the same way as the stirrer. The large cavity excited by current sources is then modeled using the DSC method. The proposed hybrid method is first applied to the analysis of two-dimensional (2-D) transverse magnetic (TM) RCs. Its advantages are demonstrated using numerical examples on 2-D TM RCs. It is then used for the modeling of three-dimensional RCs. Numerical examples show that the proposed hybrid method is much more efficient than a pure MoM-based commercial software. In order to further reduce the memory requirement, a hybrid technique combining recursive update DSC (RUDSC) method and MoM is developed. In the hybrid RUDSC-MoM, the DSC unknowns are first eliminated using a layer-based elimination algorithm, and the MoM unknowns are solved by a direct solver. The RC is then equivalent to a large cavity excited by known current sources, which is modeled by adopting the RUDSC method. In the layer-based elimination algorithm, the cavity is divided into many layers along its longest direction, and DSC unknowns are eliminated layer by layer. Employing the local property of differential operators, the layer-based elimination algorithm requires low memory cost. Meanwhile, the RUDSC method consumes a small amount of memory because it only needs storing two sparse differentiation matrices. With its low memory consumption, the hybrid RUDSC-MoM extends RC modeling to higher frequencies, which would be impossible using the MoM-based commercial software.